Outcomes of penetrating keratoplasty at a tertiary institution in South Africa. - Theron, Yolande (Division of General Surgery, 2024)
Aims: To determine corneal graft survival rates and visual outcomes of penetrating keratoplasty (PKP) in a South African setting. Methods: A retrospective review of 99 penetrating keratoplasties performed at Groote Schuur Hospital, South Africa over a 3-year period between February 2016 and February 2019. Results: The mean age of study participants was 38 years (14-85). The study included 60% females and 40% males. The main indications for surgery were keratoconus (58%), corneal scar (21%), regrafts (8%), pseudophakic bullous keratopathy (6%), corneal dystrophies (3%) and pellucid marginal degeneration (1%). The overall graft survival at 1-year follow up was 86%. A higher 1-year graft survival rate of 94% was seen in patients with keratoconus. The total number of patients diagnosed with graft failure at 1 year was 13.The Kaplan-Meier survival analysis was used to assess time to graft failure. The estimate was 11.7 months (mean time to graft failure) with a 95% CI confidence interval from 11.4 to 12 months. In our study, best corrected Snellen acuity in the category of 6/6-6/18 was found in 59.2% of patients 1-one year post-operatively, compared with 1% of patients in the same BCVA group pre-operatively. Patients with a BCVA equal to 3/60 or less reduced from 56% preoperatively to 20% postoperatively at 1 one year. Conclusion: Penetrating Keratoplasty is an effective long term treatment option to restore visual acuity in certain corneal disorders in a middle to low-income country. Our results demonstrated a comparable 1-year graft survival rate to high-income countries.